On Algebra, Cosmic Triangles and the shape of our Universe - Kalimuthu, S (Annals of Mathematics and Physics, 2022)
The curvature parameter k and the density parameter omega play the dominant phenomena determining the fate of our universe. According to these two scales, the geometry of the universe has three possibilities namely, flat, open, or closed. The flat and open universe will have continual expansion. But the closed universe will turn around and collapse. If k is zero, the universe is flat, if it is greater than zero, it is closed and if k is less than zero the universe will be open. And if the density parameter Omega is one (1), the universe is flat, if it is greater than one, the universe will be closed and if it is less than one, the universe is open. The main thing is that if the sum of the interior angles of the cosmic triangles is equal to 180 degrees, the geometry of our universe is flat /Euclidean If it is less than 180 degrees, the shape of our universe is open/ hyperbolic and if it is greater than 180 degrees it is closed/elliptic. In this short work, by applying the fundamental operations of classical algebra to the cosmic triangles, the author attempts to prove that the shape of our universe is flat.